Наративна модель «Сонячної машини» Володимира Винниченка: реалізація амбівалентності ідейного задуму - Крикун, Л. (Літературознавчі обрії. Праці молодих учених, 2010)
The article reveals the practical ambivalence of the author’s conceptual idea of happiness in the novel «Sunny machine» with the help of narrative approach. Communicative Wolf Schmid’s scheme is used to cover all the peculiarities of narrator’s functioning in the novel at the level of message. Volodymyr Vynnychenko made an attempted to implement socialistic principles and ideas (sonceism) through experimenting, they were supposed to make the person happy. Unfortunately, these attempts appeared to be not realized in reality. Therefore, idea of universal happiness lives in author’s dreams and beliefs, waiting to arise in his consciousness.